SaUspA, the Universal Stress Protein of Sulfolobus acidocaldarius Stimulates the Activity of the PP2A Phosphatase and Is Involved in Growth at High Salinity - Ye, Xing; van der Does, Chris; Albers, Sonja-Verena (Frontiers in Microbiology, 2020)
In Sulfolobus acidocaldarius, the protein phosphatase PP2A plays important regulatory roles in many cellular processes, including cell growth, cell shape and synthesis of the archaellum. A conserved prokaryotic protein, designated as SaUspA, was identified as an interaction partner of the phosphatase PP2A. SaUspA belongs to the universal stress protein (USP) superfamily, members of which are found in bacteria, archaea, plants and invertebrates. Biochemical analysis showed that SaUspA is a homodimeric ATP-binding protein, which also in vitro binds to PP2A. SaUspA did not hydrolyze ATP, but stimulated the phosphatase activity of PP2A and might in this manner affect many other processes. Interestingly, binding of ATP further enhanced SaUspA’s interaction with PP2A. In contrast to bacterial usp genes, environmental stress conditions including stationary phase, starvation stress, high salinity stress and UV stress did not stimulate expression of saUspA. Deletion of saUspA led to premature production of the archaellin FlaB in S. acidocaldarius although motility was not affected. The ΔsaUspA mutant showed a significant growth defect under high salinity stress and complementation of ATP-binding deficient mutant SaUspAG97A failed to restore this growth defect. Compared with the wild type strain, its growth or survival was not affected under heavy metal stress and UV stress. To date, this is the first study in which the physiological role of USP homologs in archaea have been reported.